2017
DOI: 10.5004/dwt.2017.21786
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microbial and physiochemical quality of ballast water in commercial ships entering Bushehr port, along the Persian Gulf

Abstract: a b s t r a c tIn the present study to evaluate ballast water impacts on coastal areas, samples were taken from commercial ships entering Bushehr port along the Persian Gulf. Standard methods were used for analyses of total and fecal coliforms, Pseudomonas, heterotrophic plate count (HPC), alkalinity, and hardness. Other parameters such as TOC, salinity, EC and TDS were also determined. The levels of TDS, EC, alkalinity, total hardness, salinity and TOC ranged from 3790-14510 mg/L, 5690-21760 μS/ cm, 104-191 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Positive number 19 4 3 14 0 demonstrated the higher efficiency and accuracy of PCR method as compared to conventional culture methods, and this method can reduce the time and cost required for the specific diagnosis. Bushehr port 34 ports all of the world Total coliform, Fecal coliform, HPC, P. aeruginosa [6] According to International Maritime Organization (IMO) guideline, all ships should discharge and re-watering ballast water tanks in open waters before entering the destination port and coastal areas to prevent the transmission of pathogenic species and damage the marine environment. IMO has also suggested the regulation to limit the concentrations of living organisms that may be discharged by ballast water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive number 19 4 3 14 0 demonstrated the higher efficiency and accuracy of PCR method as compared to conventional culture methods, and this method can reduce the time and cost required for the specific diagnosis. Bushehr port 34 ports all of the world Total coliform, Fecal coliform, HPC, P. aeruginosa [6] According to International Maritime Organization (IMO) guideline, all ships should discharge and re-watering ballast water tanks in open waters before entering the destination port and coastal areas to prevent the transmission of pathogenic species and damage the marine environment. IMO has also suggested the regulation to limit the concentrations of living organisms that may be discharged by ballast water.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the amount of ballast water discharged into oceans and coastal waters has increased around the world [5]. So the transmission of pollutants and microorganisms through ballast water has recently been known as a global concern [6,7]. Recent studies have reported a high bacterial diversity in ballast water [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It also indicated PCR assays as an appropriate alternative to conventional culture methods, which provide quick and accurate data for human health protection procedures [ 14 ]. Additionally, the presence of high levels of metabolites and organic matter in the water of ballast tanks create favorable conditions for the development of opportunistic bacteria groups, which leads to a reduction in microbiological competition within these closed spaces [ 15 , 16 , 17 , 18 , 19 ]. New interpopulation interactions may promote disruption of the pattern of interspecies distribution in local waters.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the low number of reports, we should also bear in mind that ballast water can be a source of chemical pollution [ 19 , 20 , 21 , 22 ]. High concentrations of heavy metals (e.g., Cr, Pb, and Hg) and ions in ballast water may affect the health of aquatic organisms that are subsequently consumed by humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation